2007
DOI: 10.1590/s1517-83822007000200009
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of an enzyme complex from a new strain of Clostridium thermocellum with emphasis on its xylanase activity

Abstract: A new bacterial strain (ISO II) was isolated from manure cow and identified as phylogenetically close to the thermophilic cellulolytic bacterium Clostridium thermocellum. The new strain produced extracellular xylanase, pectinase, mannanase and cellulase activities when grown in liquid culture medium containing banana stem as carbon source. The enzyme production profile after growth on banana stem showed that xylanase and cellulase activities were detected in different incubation periods. An enzyme complex cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…The presence of L-tryptophan in the reaction mixture increased xylanase activity by 37%, and a similar increase was observed for cysteine, confirming the presence of reduced thiol (cysteine) in the enzyme structure [13]. Similar results were found in the characterization of xylanase from Acrophialophora nainiana [65], which was demonstrated to be activated by cysteine and tryptophan; Clostridium thermocellum [64], which is activated by cysteine, tryptophan, and DTT; Penicillium capsulatum [25], which is activated by cysteine and DTT; Aspergillus niger, Penicillium corylophilum and Trichoderma longibrachiatum [11], which are activated by 9.3 mM of cysteine and tryptophan; and Trichoderma harzianum [24], which is activated by 20 mM of cysteine and DTT. Tests with xylanase from Streptomyces, Bacillus, and Chainia [20,35] revealed the involvement of tryptophan and cysteine residues in the active sites.…”
Section: Xylanase Hydrolytic Profilesupporting
confidence: 78%
See 1 more Smart Citation
“…The presence of L-tryptophan in the reaction mixture increased xylanase activity by 37%, and a similar increase was observed for cysteine, confirming the presence of reduced thiol (cysteine) in the enzyme structure [13]. Similar results were found in the characterization of xylanase from Acrophialophora nainiana [65], which was demonstrated to be activated by cysteine and tryptophan; Clostridium thermocellum [64], which is activated by cysteine, tryptophan, and DTT; Penicillium capsulatum [25], which is activated by cysteine and DTT; Aspergillus niger, Penicillium corylophilum and Trichoderma longibrachiatum [11], which are activated by 9.3 mM of cysteine and tryptophan; and Trichoderma harzianum [24], which is activated by 20 mM of cysteine and DTT. Tests with xylanase from Streptomyces, Bacillus, and Chainia [20,35] revealed the involvement of tryptophan and cysteine residues in the active sites.…”
Section: Xylanase Hydrolytic Profilesupporting
confidence: 78%
“…The purified xylanase preparation was also tested against 1% (w/v) 4-O-methyl-D-glucurono-D-xylan, pNPG, CMC, pectin, and 0.5% (w/v) galactomannan in routine assay conditions. Filter paper (FP) and microcrystalline cellulose (Avicel) were also tested [64].…”
Section: Xylanase Productionmentioning
confidence: 99%
“…Yeast 18Y, which showed the highest endo-xylanase activity, was submitted to sequencing of the D1/D2 domains of the large subunit of the rRNA gene, and identified as Cryptococcus laurentti. Studies using microorganisms for xylanase production are mainly performed using filamentous fungi (Guimarães, 2006) and bacteria (Vieira, 2007). The yeasts described in the literature as producing endo-xylanase include Trichosporon (Stevens, 1977), Pichia stipitis (Lee et al, 1986), Aureobasidium pullulans (Leathers et al, 1986), Cryptococcus albidus (Biely, 1980), and Cryptococcus flavus (Parachin et al, 2009;Yasui, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Morag et al reported that the activity of xylanase in the cellulosome of C. thermocellum reached a maximum in the pH range between 6.0 and 7.5. Other researchers showed more precise values to be pH 6.5 and 6.0 …”
Section: Resultsmentioning
confidence: 90%
“…It has been demonstrated from extensive studies on model compounds found in hydrolyzates of lignocellulosics that C. thermocellum can convert high molecular weight compounds such as cello‐oligosaccharides and xylo‐oligosaccharides into lower molecular weight compounds . Clostridium thermoaceticum , in turn, can ferment these obtained compounds, together with other low molecular weight products such as monosaccharides, decomposed products, and organic acids, into acetic acid .…”
Section: Introductionmentioning
confidence: 99%